BIOLOGICAL PARAMETERS OF Sarcophaga carnaria L. (DIPTERA: SARCOPHAGIDAE) NECROPHAGOUS FLY BREEDING ON TWO PIG SUBSTRATES (Sus scrofa domesticus L.) AT THE NATIONAL FLORISTIC - DAO, HASSANE; ABOUA, LOUIS ROI NONDENOT; KOFFI, ALEXANDRE FRANKLIN; YAPO, YAPIBIE CARINE EURUDICE (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
The need to elucidate the crimes, led us to study the necrophagous insects including Sarcophaga carnaria, a larviparous fly. These develop while consuming the decaying corpse. This gives them great importance in forensic entomology. The aim of our study is to determine the biological parameters of S. carnaria. The work took place at the national floristic center, located at the Félix Houphouët Boigny University. Follow-up was done from 3 september 2015 to 11 november 2015. The total development time of S. carnaria was 16.07 ± 0.19 days on the liver at an average temperature of 26.92 ± 1.9°C and an average relative humidity of 85.08 ± 3.1 % whereas it was 17.12 ± 32 days on the striated muscle at the same temperature and relative humidity. The rate of emergence on the liver was 77.55 ± 3.40 % on the liver whereas on the striated muscle it was 63.84 ± 3.68 %. The sex-ratio of S. carnaria on pig liver was 0.80 ± 0.03 and on striated muscle was 0.95 ± 0.06. The life expectancy of males and females gave 16.76 ± 0.84 days and 20.23 ± 0.77 days on the liver, whereas on striated muscle, Was 14.33 ± 0.21 days and 17.03 ± 0.36 days at an average temperature of 26.15 ± 0.71°C and an average relative humidity of 86.23 ± 1.3 %.